Assessment of the effectiveness of management of innovative development institutions at the meso level - Yu. A. Abutalipova (Вестник университета)
The purpose of the study is to identify the specifics of the management of technological platforms, in particular, in the light and textile industries, and to evaluate the effectiveness of innovation development institutions' functioning at the meso level. The methodological basis of the study was modern scientific approaches to aevaluating the effectiveness of innovation development institutions' functioning, evaluating the effectiveness of technology platform management systems: descriptions, structural-functional and system analysis, cause-and-effect relationships, cluster and factor analysis. To achieve this goal, a simulation of evaluating the effectiveness of technological platforms has been carried out, because of which 3 types of Russian platforms were revealed, the management of the development of which requires a differentiated approach. Since the technological platform “Textile and Light Industry” occupies a leading position in the rating of Russian technological platforms, the industry development's dynamics, allowing to evaluate the impact of communication platform functioning on Russian industrial complex development, was studied. To assess the effectiveness, it was planned to form a comprehensive indicator of of light industry development based on the results of factor analysis (by the method of principal components). It has concluded that the creation and development of a technological digital environment contribute to the effective interaction between various sectors of the economy and market entities, which is based on regulatory and legal regulation, ensuring information security, developing innovative infrastructure, providing highly qualified personnel in the industry.